2021
DOI: 10.1186/s12891-021-04388-1
|View full text |Cite
|
Sign up to set email alerts
|

Reverse wedge effect following intramedullary nail fixation of trochanteric fracture, what does it imply?

Abstract: Lag screw cut-out is the most common cause of fixation failure of trochanteric fractures. Intraoperative assessment of fracture reduction and fixation quality is vital to avoid fracture reduction and achieve good functional outcomes. In a recent study, Zhang et al. reported the occurrence of a reverse wedge effect after intraoperative nail insertion based on a new computed tomography(CT)-guided fracture classification system, which specifically happened to the basicervical facture type and resulted in valgus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…During the surgery, anteromedial calcar fracture gapping was frequent. Zhang et al [ 31 , 32 ] reported that an inferior medial gap (mean and standard deviation, 9.2 ± 4.6 mm) appears during intramedullary nailing in basicervical trochanteric fractures, called the reverse wedge effect. In addition, inferior placement of the guidewire is beneficial for acquiring an ideal Cal-TAD.…”
Section: Discussionmentioning
confidence: 99%
“…During the surgery, anteromedial calcar fracture gapping was frequent. Zhang et al [ 31 , 32 ] reported that an inferior medial gap (mean and standard deviation, 9.2 ± 4.6 mm) appears during intramedullary nailing in basicervical trochanteric fractures, called the reverse wedge effect. In addition, inferior placement of the guidewire is beneficial for acquiring an ideal Cal-TAD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we demonstrated that a PMCS effect is prone to produce coxa valga, while neutral (NP) and negative medial cortical effects (NMCS) are closely related to coxa vara. As we proposed before 5 , intraoperative maneuvers play an essential role in creating these phenomena. Although provisional fracture-maintaining techniques have been used for cases that could not be well reduced through closed reduction, coincidence among the trajectory of the IM nail and fracture line make intramedullary reaming become ineffective.…”
Section: Discussionmentioning
confidence: 87%
“…However, femoral lateralization could not be eliminated during a manual change of neck-shaft angle from wedge effect (coxa vara) to reverse wedge effect (coxa valga) intraoperation. As we proposed before 5 , the appearance of femoral lateralization maybe arise from disruption of the primary tensile trabeculae at the superolateral part of the femoral neck fragment, where it courses horizontally and perpendicularly to the longitudinal axis of the proximal femur. Due to the weaker cancellous bone structure at the great trochanter, an outward pushing force would inevitably be generated medially to laterally when the nail contacts the superolateral cortex of the femoral neck fragment during nail insertion into the medulla.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation